Electronic properties of DNA from selected Pleurotus species using DNA specific schottky diodes/ Nastaran Rizan - Nastaran Rizan, Rizan (2021)
The exciting discovery of the semiconducting-like properties of deoxyribonucleic acid (DNA) and its potential applications in molecular genetics and diagnostics in recent times has resulted in a paradigm shift in biophysics research. In this aspect, recent studies are being conducted towards detecting charge transfer mechanism to understand the electronic properties of DNA based on its sequence-specific electronic response. This current research aims to contribute towards this effort by fabricating and developing DNA-specific Schottky barrier diodes for characterizing and identifying mushrooms using current-voltage (I-V) profiles. Selected electronic properties such as ideality factor, barrier height, shunt resistance, series resistance, turn-on voltage, knee-voltage, breakdown voltage and breakdown current were calculated. The data was further utilized to quantify the identification process as compared to conventional morphological and molecular characterization techniques. Conventional techniques are used in order to study biodiversity, but sometimes it can be misleading and unreliable and is not sufficiently useful for the identification of mushrooms genera especially for identification of closely related species in genus Pleurotus. In this research, genomic DNA as well as amplified specific regions (internal transcribed spacer, large subunit ribosomal DNA and large subunit of ribosomal polymerase II) of selected species of Pleurotus were subjected to IVmeasurements. Both genomic and amplified DNA showed distinct profiles corresponding to each species. However, comparison of I-V profiles of genomic and amplified DNA suggested that genomic DNA is a better choice for electronic identification of species. This is mainly due to more base pair differences between genomic DNA of different species. High similarity in the conserved regions showed a closer yet distinguishable electronic profile for each species. The electronic profiles, both in the negative and positive bias regions were however found to be highly characteristic according to the base-pair sequences. However, DNA charge transfer are significantly regulated by pH fluctuations which influences the stability of the double helix structure and strongly attenuated its electronic profile. To investigate the pH influence, genomic DNAs integrated within an aluminium (Al)-indium tin oxide (ITO) Schottky junction was prepared and its electronic profiles studied. Although DNA is known to be reasonably stable in aqueous solution, environmental factors can also affect the helical structure resulting in significantly attenuated electronic profiles. DNA molecules are not stable when stored for long periods in solution form at room temperature (RT) prompting much interests for solvents in which DNA structures exhibit long-term stability. Ionic liquid (IL), 1-butyl-3-methylimidazolium acetate ([BMIM][Ace]) is a potential solvent that ensure long-term stability of DNA. Therefore, the effect of IL on genomic DNAs was investigated by using the I-V profiles. Furthermore, various solid-state parameters calculated allow us to understand the charge transfer mechanism in DNA molecules as a function of pH conditions and IL, which could act as a potential indicator for various stages of DNA functionality.